OPTIMIZATION OF THE STACKER PARAMETERS OF THE POMEGRANATE BURYING MACHINE USING THE METHOD OF MATHEMATICAL PLANNING OF EXPERIMENTS - Abdunazarov Elbek Elmurodovich (Web of Journals Publishing, 2025)
The article presents the results of optimizing the parameters of the soil stacker of a machine designed for covering pomegranate bushes with soil, based on the method of mathematical planning of experiments. The optimization was conducted using a multi-factor experimental design, which allowed the determination of the most effective working parameters that ensure high-quality performance and minimal energy consumption.
Keywords: machine for covering pomegranate bushes, soil compaction device, degree of bush damage, soil ridge density, ridge height, ridge width, covering thickness, stacker. are reduced to a level that is ineffective for their induction, and therefore they can degrade even low concentrations of pollutants